Corporate Codes of Conduct: The Effects of Code Content and Quality on Ethical Performance - Erwin, Patrick M. (2011)
Corporate codes of conduct are a practical corporate social responsibility (CSR) instrument commonly used to govern employee behavior and establish a socially responsible organizational culture. The effectiveness of these codes has been widely discussed on theoretical grounds and empirically tested in numerous previous reports that directly compare companies with and without codes of conduct. Empirical research has yielded inconsistent results that may be explained by multiple ancillary factors, including the quality of code content and implementation, which are excluded from analyses based solely on the presence or absence of codes. This study investigated the importance of code content in determining code effectiveness by examining the relationship between code of conduct quality and ethical performance. Companies maintaining high quality codes of conduct were significantly more represented among top CSR ranking systems for corporate citizenship, sustainability, ethical behavior, and public perception. Further, a significant relationship was observed between code quality and CSR performance, across a full range of ethical rankings. These findings suggest code quality may play a crucial role in the effectiveness of codes of conduct and their ability to transform organizational cultures. Future research efforts should transcend traditional comparisons based on the presence or absence of ethical codes and begin to examine the essential factors leading to the effective establishment of CSR policies and sustainable business practices in corporate culture.
Keywords: CSR ranking system; Ethical Performance; code quality; code content; codes of ethics; codes of conduct